Assessment of risk to school buildings resulting from distant earthquakes - Tan, K.T.; Abdul Razak, H. (2011)
The effects of far distant earthquakes felt in regions with low and moderate seismicity has increased markedly over the last decade. Henceforth fragility curves in this study are to indicate whether buildings are safe to enter or not after an earthquake event occurring more than 300km away. The probability of light, moderate and severe damage states occurring on two and four storey reinforced concrete buildings up to a peak ground acceleration of 0.2g were predicted. The building models were constructed using finite element software based on eight node brick elements with three degrees of freedom at each node. The analysis was carried out using a dynamic response spectrum to calculate the peak inter-storey drift ratios. For the development of fragility curves, the results were collated following a log-normal mean distribution. The results showed that light damage is likely to occur with a probability of over 10 within a 50 year period, while the existing record is unlikely to cause structural damage. The fragility curves were comparable to those for RC moment resisting frames obtained by (Rossetto and Elnashai 2003) at a lower drift limit, with approximately 2 of inter-storey drift ratio.